2007
DOI: 10.1242/dev.004390
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal development is initiated by Cited2 and Wt1 through modulation of Sf-1 dosage

Abstract: It has been proposed that the mammalian adrenal cortex and gonad are derived from the same primordium present during early urogenital development. Molecular pathways involved in the differentiation of the adrenal cortex from the adrenogonadal primordium (AGP) have yet to be determined. Here we show in mice that the transcription co-factor Cited2 is required for the specification of the adrenal cortex from the AGP. We present genetic and molecular evidence demonstrating that Cited2 interacts with the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 48 publications
(69 reference statements)
8
127
0
2
Order By: Relevance
“…1a,b). Consistent with previous reports [18][19][20][21] , the treated cells were decreased in number, probably due to decreased proliferation (Fig. 1c,d).…”
Section: Resultssupporting
confidence: 93%
“…1a,b). Consistent with previous reports [18][19][20][21] , the treated cells were decreased in number, probably due to decreased proliferation (Fig. 1c,d).…”
Section: Resultssupporting
confidence: 93%
“…We demonstrated that this essential role of Cited2 was dependent on its physical and functional interaction with Wt1 in the AGP, prior to adrenal formation. This interaction resulted in increased Sf-1 promoter activity and Sf-1 expression [20] (Fig2). Other studies have shown that modulations of Sf-1 dosage can affect gonadal and adrenal development to different degrees.…”
Section: Cited2 Wt1 and Sf-1 Dosagementioning
confidence: 87%
“…In mouse, Sf-1 was detected as early as E9.0. The process of AGP development was similar and the adrenal anlage separated from the bipotential precursor at E10.5 (10-11 tail somites) [19,20] …”
Section: I-the Adreno-gonadal Primordium (Agp)mentioning
confidence: 95%
See 2 more Smart Citations